The revised 2 versus 2 small side game increases endurance performance of football players - Mustafa Furkan Ocak; Mehmet Yildiz (Revista Brasileira de Futsal e Futebol)
The current study aimed to investigate the effect of the 2 vs. 2 small side game (SSG) arranged according to the principle of 90-95% Max HR (3 sets 4x4 min) on the endurance performance and running mechanics of the elite young football players. Sixteen elite young male football players (age: 18.43±0.62 years, height: 180.68±4.54 cm, body weight: 72.00±6.40) from the Afjet Spor U-19 team participated in the study. The participants were randomly divided into Revised 2 vs. 2 SSG (experimental group, n=8) and Classic 2 vs. 2 SSG (control group, n=8) groups. While the experimental group played the Revised 2 vs. 2 SSG for four weeks, two days a week, the control group played the Classic 2 vs. 2 SSG. Before and after the application, the cardiovascular endurance values of the participants were evaluated by considering the Yo-Yo 1 test and the kinematic (distance covered, sprint number, and rates in speed intervals) and physiological (%max HR) values that they exhibited during the matches. It was determined that both SSGs caused improvement Yo-Yo IR1 test (time: F=17,72, p>0,001),  total distance covered  (time F: 3.62, P<0.001),  distance covered in the speed zone at 14.00 - 19.99 km/h (group F= 10.177, p<0.007), and distance covered at the speed zone at 20.00 - 49.99 km/h (time F= 19.832, p<0.001). However, a greater extent was seen in the revised SSG for the total distance covered (group✻time interaction F:0,016, P<0.016) and distance covered in the speed zone at 20.00-49.99 km/h (group✻ time interaction F=11.241, p=0.005), without causing a significant change in the physiological values of the football players. It is recommended to use the Revised 2 vs. 2 SSG to improve endurance performance in football training.